2019
DOI: 10.2474/trol.14.71
|View full text |Cite
|
Sign up to set email alerts
|

Friction Control by Applying Electric Potential under Lubrication with Ionic Liquids

Abstract: This study investigated the effects of the electric potential of a surface on the lubricating capabilities of ionic liquids. The friction coefficient of 1-butyl-3-methylimidazolium iodide was unchanged by the electric potential of the surface because this ionic liquid has difficulty moving in a solution owing to its low conductivity. However, the friction coefficient, when lubricated with 1-butyl-3-methylimidazolium tris(pentafluoroethyl)trifluorophosphate and 1-butyl-3-methylimidazolium hexafluorophosphate, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In the cases of [HMIM][BF 4 ] and [OMIM][BF 4 ] with longer alkyl chains, the friction coefficient of the applied surface potential increased compared to that of OCP. When no potential is applied, ionic liquids form the adsorption layer and have cations and anions aligned side by side on the worn surfaces [27,29,30]. It is considered that these adsorption layer exhibit the lowest friction.…”
Section: Potential Windows Of Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cases of [HMIM][BF 4 ] and [OMIM][BF 4 ] with longer alkyl chains, the friction coefficient of the applied surface potential increased compared to that of OCP. When no potential is applied, ionic liquids form the adsorption layer and have cations and anions aligned side by side on the worn surfaces [27,29,30]. It is considered that these adsorption layer exhibit the lowest friction.…”
Section: Potential Windows Of Ionic Liquidsmentioning
confidence: 99%
“…In pure rolling friction tests, the thickness of the boundary lubrication layer varied according to the surface potential [28]. It was observed that the friction coefficient varied with low contact pressure (the order of several hundred kPa) under sliding friction conditions [29].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their purely ionic composition, ILs interact strongly with surfaces, which lead to the formation of tribologically protective layers 45 . These interactions can be controlled by applying electrical potentials, which influences the tribological behaviour 46‐51 . Some wear additives such as ZDDP have synergetic effects with ILs 45 .…”
Section: Introductionmentioning
confidence: 99%
“…45 These interactions can be controlled by applying electrical potentials, which influences the tribological behaviour. [46][47][48][49][50][51] Some wear additives such as ZDDP have synergetic effects with ILs. 45 From an environmental point of view, the addition of graphene to ILs should also be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new challenges have emerged regarding the use of ionic liquids as lubricants. For example, the control of the friction surface potential using these liquids as additives was investigated [27][28][29][30][31][32][33][34][35]. In addition, as a very important challenge, it is necessary to evaluate the effect of moisture on the friction properties of an ionic liquid.…”
Section: Introductionmentioning
confidence: 99%